Burnout, Organizational Self-Efficacy and Self-Esteem among Brazilian Teachers during the COVID-19 Pandemic - Henrique Pereira; Vivianne Oliveira Gonçalves; Renata Machado de Assis (MDPI AG, 2021)
The purpose of this study was to assess the prevalence of, and the association between burnout, organizational self-efficacy and self-esteem, and to assess the predictive influence of burnout and organizational self-efficacy on self-esteem among Brazilian teachers during the COVID-19 pandemic. Brazilian teachers (n = 302) between 24 and 70 years old (Mage = 46.75, SD = 11.02) participated in this study. Measurement instruments included a sociodemographic questionnaire, the Burnout Assessment Tool, the Organizational Self-Efficacy Scale and the Rosenberg Self-Esteem Scale. The prevalence of burnout symptoms was 3.2%, the prevalence of low occupational self-efficacy was 21.5%, and the prevalence of low self-esteem was 2.7%. Significant correlations were found between all variables under study. Hierarchical linear regression analysis showed that overall levels of burnout explained 40% of the variance of self-esteem, while together with organizational self-efficacy, it explained 55%. This study presents evidence of the impact of overall levels of burnout and self-efficacy on teachers' self-esteem and also contributes to the body of knowledge under construction about the scenario perceived by teachers in Brazil during the COVID-19 pandemic.